Effect of Dust and Particulate Matter on Evaporator Coil Performance (University of Khartoum Engineering Journal, 2022)
Air conditioning is responsible for substantial electricity consumption and peak demand in conditioned spaces. Evaporator coils are most common in air conditioners and absorb heat when air is passed through them. One area which has been neglected by researchers is fouling of evaporator and condenser coils. This paper investigates experimentally the effect of dust and particulate matter on the performance of an evaporator coil before and after cleaning of it. The experimental results indicated that the stability of temperature distribution, humidity and reduction in power consumption occurred when the coil surface is cleaned regularly and kept free of fouling particles.